"There is No Corona; It's a Conspiracy": Addressing the Perceptions of People about COVID-19 through the Narrative of Their Comments on Social Media. Issue 1 (2nd January 2021) - Al-Motlaq, Mohammad A.
Abstract: This study explored peoples perspectives of COVID-19 through the narrative of their comments on social media. The study employed a qualitative content analysis of a convenience sample of comments attached to more than 10 COVID-19 posts in two official Facebook pages of both Jordanian and Australian main media in May, 2020. The reactions to each post ranged between 60 and 701 reactions at the time of analysis. Most responses were pessimistic and negative supporting a theory of conspiracy. An important outcome though was the presence of a counter conspiracy voices making some kind of equilibrium. While major recommendations included improving public awareness and attitudes, an important action to ensure equilibrium between negative and positive voices is identifying strategies to improve access to credible and relevant health information. A culture of evidence based facts need to be spread among everyone to be able to address this point and gain people's trust.